Polyamines deficient diet is a complementary strategy in fighting cancer: analysis on selected medicinal fruits - Abdul Ghani, Radiah; Jamil, Elyna Fatini; Ibrahim, Muhammad (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Polyamines are one of the oldest substances known in biochemistry consist of putrescine, spermidine and spermine. They are essential components of all living cells primarily involve in cell growth and proliferation. Upregulation of polyamines in human body is highly associated with various diseases, including cancer. Therefore, polyamines deficient diet (PDD) has become one of the strategies to inhibit carcinogenesis. This study was aimed to determine the polyamines content in selected anticancer fruits and their effect on polyamine polyamine metabolic enzymes was explored in human lung adenocarcinoma cells (A549). In this study, the selected medicinal fruits are Phoenix dactylifera (ajwa dates),Ficus auriculata (fig),Beta vulgaris (beetroot), Ziziphus jujube (jujube) and Vitis vinifera (raisin). The selected medicinal fruits were initially grouped into classes based on total polyamines content using High performance Liquid Chromatography (HPLC). The ability of selected fruits to reduce A549 intracellular polyamines was determined using the same technique. Accordingly, changes in polyamine metabolic enzymes activities; ornithine decarboxylase (ODC) and spermidine/spermine N-acetyltransferase (SSAT) were measured correspondingly using quantitative polymerase chain reactions (qPCR). Results suggested Beetroot, ajwa dates, fig and raisin are classified as low polyamines fruits while jujube demonstrates high content of polyamines. Significant decreased of total intracellular polyamine content after 24 h of treatments with these fruits were identified when compared with untreated A549 cells.Ornithine decarboxylase (ODC) activity showed downregulation upon treatment with ajwa dates, jujube and raisin while SSAT activity displayed alterations in beetroot and jujube treated A549 cells. Thus, we concluded that beetroot, ajwa dates, fig and raisins are the promising candidates for PDD strategy for their low polyamines, ability to reduce A549 intracellular polyamines and modification on ODC and SSAT activities.